Pengaruh Kualitas Website dan Kualitas Pelayanan Terhadap Kepuasan Pelanggan Pada PT. Optima Cipta Sertifikasi - Syahrul Maulana; Aldila Rahma Putri (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This study aims to determine the effect of Website Quality and Service Quality both partially and simultaneously on Customer Satisfaction at PT. Optima Cipta Sertifikasi. The method used is quantitative. The sampling technique uses the slovin formula with a sample size of 127 respondents. Data collection by questionnaire, and data analysis techniques with validity tests, reliability, classical assumption tests, simple regression analysis, multiple regression, hypothesis tests t-test, f-test, and coefficient of determination. The results of this study indicate that website quality has a significant effect on customer satisfaction. This can be proven that t count> t table (10.966> 1.979) From the results of the simple linear regression analysis, the regression equation Y = 11.859 + 0.665X1 was obtained, the regression coefficient value of 0.665 was obtained indicating that partially the (positive) effect. and service quality has a significant effect on customer satisfaction, this can be proven that t count> t table (11.458> 1.979). And the value of the regression equation Y = 10,350 + 0.714X2 is obtained, so the regression coefficient of 0.714 indicates that partially the influence is (positive), while simultaneously the quality of the website and the quality of service have a significant effect on customer satisfaction with the regression equation Y = 7,324 + 0.357X1 + 0.435X2, indicating a (positive) influence. And the results of the hypothesis test obtained the value of f count> f table or (84,013> 3.07), while the results of the determination coefficient of 0.575%, it can be concluded that the quality of the website and the quality of service have a significant effect on the customer satisfaction variable of 57.5%, while the remaining 42.5% is influenced by other factors.